'Just so you know, the patient is staff': healthcare professionals' perceptions of caring for healthcare professional–patients. Issue 1 (19th January 2016) - Svantesson, Mia; Carlsson, E; Prenkert, M; Anderzén-Carlsson, A
Abstract : Objective: To explore healthcare professionals' conceptions of the care of patients who are also healthcare professionals. Design: Explorative, with a qualitative, phenomenographic approach. Participants and setting: 16 healthcare personnel within different professions (doctors, nurses, assistant nurses, physiotherapists, occupational therapists) were interviewed about the care of 32 patients who were themselves members of different healthcare professions, in one healthcare organisation in Sweden. Results: The care of patients who are healthcare professionals was conceived in five different ways, as: usual, dutiful, prioritised and secure, insecure and responsive. An initial conception was that their care was usual, just as for any other patient, and also a perceived duty to treat them and to protect their right to be a patient—as any other patient. Exploring further, informants described that these patients did receive secure and prioritised care, as the informants experienced making a greater commitment, especially doctors giving privileges to doctor–patients. A conception of insecure care infused the informants' descriptions. This comprised of them feeling intimidated in their professional role, feeling affected by colleagues' stressful behaviour and ambiguity whether the healthcare professional–patient could be regarded as a competent professional. The deepest way of understanding care seemed to be responsive care, such as acknowledging and respecting the patient's identity and responding to their wishes of how treatment was to be met. Conclusions: Caring for healthcare professionals seems to trigger different ethical approaches, such as deontology and ethics of care. According to ethics of care, the findings may indeed suggest that these patients should be cared for just as any other patients would be, but only if this means that they are cared for as persons, that is, they are given 'person-centred care'. This would imply balancing between acknowledging the vulnerable patient in the colleague and acknowledging the identity of the colleague in the patient.